Does Exposure to Economics Bring New Majors to the Field? Evidence from a Natural Experiment - Hans Fricke; Jeff Grogger; Andreas Steinmayr (Institute for the Study of Labor (IZA), 2015)
This study investigates how being exposed to a field of study influences students' major choices. We exploit a natural experiment at a Swiss university where all first-year students face largely the same curriculum before they choose a major. An important component of the first-year curriculum that varies between students involves a multi-term research paper in business, economics, or law. Due to oversubscription of business, the university assigns the field of the paper in a standardized way that is unrelated to student characteristics. We find that being assigned to write in economics raises the probability of majoring in economics by 2.7 percentage points, which amounts to 18 percent of the share of students who major in economics.
Keywords: A20; I20; I23; 330; major choice; economics; law; higher education; gender differences